Temperature Effects on Race Determination in Heterodera glycines - Palmateer, A J (Journal of nematology, 2000)
Currently there are 16 possible races for Heterodera glycines, and these are differentiated based on ability of a nematode population to develop on a set of four differential soybean genotypes. Because results are based on numbers of nematode females that develop to a specific stage rather than on the reproductive capability of these females, race determinations based on female indices may not represent results obtained after several reproductive cycles of H. glycines. Counting numbers of eggs and juveniles, and then developing corresponding indices, would allow reproduction to be considered in making race determinations. Our objectives were to compare the present race identification scheme for H. glycines based on female indices with those using egg and juvenile indices and to examine the effect of temperature on race designations using female, egg, and juvenile indices. Race designations for H. glycines populations from two locations in Illinois were determined at 20, 27, and 30 degrees C in a water bath. The numbers of females, eggs, and juveniles (at 19 days) were recorded, and an index based on each life stage was calculated. Race determinations based on female, egg, or juvenile indices were inconsistent when conducted at 20 degrees C, which demonstrates that this temperature is not suitable for identifying races of H. glycines. However race designations at 27 and 30 degrees C were consistent for all three indices. This indicates that counting females, eggs, or juveniles should be equally reliable when race determinations are conducted at these two temperatures, and choice of method would depend on investigator preference or research objective